SCREENING ATHLETES WITH PATELLAR TENDINOSIS: CLINICAL INFORMATION TO GUIDE PREVENTIVE ATTITUDES. Issue 7 (11th March 2014) - Mendonça, L; Bittencourt, N; Zuin, A; Barreto, R; Ocarino, J; Fonseca, S
Abstract : Background: Patellar tendinosis is a degenerative condition that could lead to tendon rupture. Conservative treatment is long-term and surgery may be required to enhance tissue regeneration. Therefore, the athlete could have his/her successful career jeopardized. Some clinical tests, usually used in patellar tendon assessment, could be associated to patellar tendon morphologic abnormalities (PTA). However, their relationship to PTA is not established and they could be used in sports practice as a strategy for preventive care. Objective: To investigate the association of VISA-P questionnaire, single-leg decline squat test and patellar tendon pain history to tendon morphological abnormalities at ultrasound. Design: Cross-sectional study. Setting: Athletes filled in VISA-P questionnaire, performed the single-leg decline squat test (SLDS) and informed about patellar tendon pain history. Athletes with Osgood-Schlater and/or Siding-Larsen-Johansson disease were excluded. An experienced examiner performed the ultrasonographic exam in tendon sagittal and transverse planes. Tendons that presented hypoechoic areas and thickness were considered as positive for morphological abnormalities. Participants: 43 athletes (26 volleyball, 14 basketball, 3 running) participated in this study, 38 males and 5 females, mean age of 24.8±6.7 years, weight of 87.6±13.7 kg and height of 1.93 ±0.1 m. Risk factor assessment: VISA-P, single-leg decline squat test and patellar tendon pain history. Main outcome measurements: Patellar tendon hypoechoic areas and thickness at ultrasound. Results: Significant associations to PTA were found. VISA-P showed an OR of 5.4 (1.3–26), SLDS of 3.8 (1.4–11) and pain history of 7.5 (1.6–42). Therefore, an athlete who presents a score under 80 points at VISA-P, for example, have 5.4 more chance to present PTA compared to an athlete that does not have PTA. Conclusions: VISA-P, SLDS and patellar tendon pain history can be easily applied in clinical practice and should be used as a screening tool in sports modalities that present a high PTA prevalence.